Problematika Penanganan Laporan Kdrt Di Kepolisian Indonesia: Perspektif Perlindungan Korban - Wahyu Sofiyani; Eko Handoyo (CV. ITTC INDONESIA, 2026)
This article examines the problems of handling domestic violence reports within Indonesian police institutions from the perspective of victim protection, with an empirical focus on reporting practices in Semarang City. The study responds to the gap between Law Number 23 of 2004 on the Elimination of Domestic Violence and victims' experiences when entering the criminal justice process. It employs an empirical juridical method with a qualitative descriptive approach. Data were obtained from legal documents, academic literature, official reports from Komnas Perempuan and the Ministry of Women Empowerment and Child Protection, victim-assistance records, and semi-structured interviews with victim advocates and police officers. The findings show that the reporting stage is still influenced by a legal culture that treats domestic violence as a private family conflict; limited victim-friendly facilities, female investigators, and referral mechanisms increase the risk of secondary victimization; and the practice of shifting evidentiary burdens to victims weakens access to justice. The discussion connects these findings with previous studies in Semarang, Palu, Yogyakarta, Bogor, Kepulauan Aru, and normative studies on the Domestic Violence Law. This article proposes a victim-protection model based on standardized initial response, risk assessment, proactive evidence-gathering, and integrated services connecting the police, local protection units, health services, and legal aid institutions.